2020
DOI: 10.1017/s1368980020003729
|View full text |Cite
|
Sign up to set email alerts
|

Designing a healthy, low-cost and environmentally sustainable food basket: an optimisation study

Abstract: Objective: Sustainable diets are diets with low environmental impacts and high affordability which contribute to food and nutrition security. The present study aimed to develop a healthy, low-cost and environmental-friendly food basket for Iran based on current consumption. Design: The Households Income and Expenditure Survey data were used. Linear Programming was utilised to obtain the optimal diets, separately, for each goal of the sustainable food basket: (1) Diet with maximum Nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Clearly, there is no obvious win-win scenario, and identifying priorities and pathways to achieve change requires careful interpretation of the results. The difficulty of identifying a dietary scenario that concurrently meets nutrient, health, affordability, and environmental goals was also reported from Iran by Eini-Zinab et al ( 34 ).…”
Section: Discussionmentioning
confidence: 81%
“…Clearly, there is no obvious win-win scenario, and identifying priorities and pathways to achieve change requires careful interpretation of the results. The difficulty of identifying a dietary scenario that concurrently meets nutrient, health, affordability, and environmental goals was also reported from Iran by Eini-Zinab et al ( 34 ).…”
Section: Discussionmentioning
confidence: 81%
“…While there is a growing body of evidence showing that increasing dairy food intake could be part of the solution to help reduce the global disease burden (37,40), there is also a growing body of evidence investigating the role of dairy foods as as sustainable source of nutrition (41)(42)(43)(44)(45)(46). These investigations have so far returned conflicting results, which largely depend on the specific foods or food groups being investigated (e.g., dairy, beef, or all animal-sourced foods), the type of modeling used (e.g., life cycle assessment, enviromental impact analysis, global foodsystem modeling), the breadth of analysis performed (e.g., a single indicator vs. multiple indicators), the specific outcomes being measured (e.g., carbon footprint per kg of food vs. per 100 kcal of food vs. per g of nutrient in a food) and where the food is produced (e.g., high-income vs. low-and-middle income countries).…”
Section: Health Outcome Country Messaging Examplesmentioning
confidence: 99%
“…While Piras et al [ 122 ] found the largest share of food to be wasted at the household level in developed countries, the waste–consumption relationship is mediated by the level of income even across the developing world. For instance, Eini-Zinab et al [ 123 ] revealed that eating more dairy products and fruits and vegetables and less bread, rice, pasta, legumes, hydrogenated fats, and sugars could reduce the total water and carbon footprints of the agricultural sector by 14% each. In lower-income communities, however, people struggle for eating rather than healthy eating, even less responsible eating.…”
Section: Discussionmentioning
confidence: 99%